Analisis Tindak Tutur Bahasa Mahasiswa dalam Interaksi Akademik dan Sosial - Dian Harahap; Eny Sihite; Lusinda Sigiro; Rotua Lumbantoruan; Talenta Sembiring; Wahyudi Rambe; Yesika Simbolon; M. Oky Fardian Gafari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study analyzes speech acts used by students in academic and social interactions. Speech acts are part of pragmatic studies that describe how language is used in everyday communication. This study aims to identify the forms, functions, and differences in the characteristics of speech acts in both contexts. The methods used in this study include observation, interviews, recording, transcription, and literature review by analyzing various relevant literature. The results of the study indicate that in academic interactions, students more often use representative and directive speech acts to convey information and give instructions, while in social interactions, they use more expressive and commissive speech acts to build relationships and express emotions. Factors that influence these differences include the context of the situation, relationships with interlocutors, the influence of media and technology, and cultural background. The conclusion of this study confirms that understanding speech acts is very important in improving the effectiveness of student communication in both academic and social environments. The implications of this study can be used to develop better communication strategies in higher education environments and increase students' awareness of the use of appropriate language in various contexts.